2013
DOI: 10.1007/s11010-013-1805-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of microRNA-9 predicts an unfavorable prognosis in human glioma

Abstract: microRNA-9 (miR-9) has been found to be upregulated along with tumor progression of gliomas by microarray-based expression profiling, and also be strongly linked to glioblastoma subtypes. However, its prognostic value in glioma is still elusive. miR-9 expression in human gliomas and nonneoplastic brain tissues was measured by real-time quantitative RT-PCR assay. miR-9 expression in glioma tissues was significantly higher than that in corresponding nonneoplastic brain tissues (P\0.001). The increased expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
3
26
1
Order By: Relevance
“…These findings appeared in agreement with a previous study by Tan et al, who reported that a balance between cyclic AMP response element-binding protein (CREB) and miR-9 determines the proliferation or migration status of glioma cells, whereby miR-9 promotes migration and CREB induces proliferation [13]. Moreover, as miR-9 expression is an independent prognostic factor for overall survival in glioma patients [14], we elected to further investigate this miRNA.…”
Section: Resultssupporting
confidence: 90%
“…These findings appeared in agreement with a previous study by Tan et al, who reported that a balance between cyclic AMP response element-binding protein (CREB) and miR-9 determines the proliferation or migration status of glioma cells, whereby miR-9 promotes migration and CREB induces proliferation [13]. Moreover, as miR-9 expression is an independent prognostic factor for overall survival in glioma patients [14], we elected to further investigate this miRNA.…”
Section: Resultssupporting
confidence: 90%
“…46 More complicated, its increased expression was shown to be a favorable prognostic factor in medulloblastoma in one report, 47 but a poor prognostic factor in glioma in another study. 48 For AML, miR-9 is the most specifically up-regulated microRNA in MLL-rearranged AML compared with other types of AML, as it is a target of MLL fusion proteins, and its expression directly correlates with disease progression. 49 In our study, miR-9 was an unfavorable prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Among the regulatory roles of miRs is the coordination of development and the parallel process, oncogenesis. MiR-9 is known to have critical roles in neuron development and migration [30] , yet has been associated with malignancies of the CNS such as GBM and Medulloblastoma [31,32] . MiR-9 also has important roles in the development of cancers outside of the CNS such as breast, colon, cervical, ovarian, and gastric cancer [3336] .…”
Section: Discussionmentioning
confidence: 99%